IMPROVING PERFORMANCE OF BISCUIT PRODUCTION PROCESS THROUGH LEAN SIX-SIGMA AT PT XYZ - Ahmad Mukti Almansur; Sukardi Sukardi; Machfud Machfud (School of Business, IPB University (SB-IPB), 2017)
This research aims to analyze waste or loss using the 7-waste approach and value added/non value added activities in the production process at PT. XYZ. This research also aims to evaluate the production process capability and sigma values at PT. XYZ and used DMAIC technique (Define, Measure, Analysis, Improvement, and Control) from Lean Six-sigma with an analysis using Failure Mode and Effect Analysis (FMEA). The results of the research obtained the values of Process Cycle Efficiency (PCE) of 47.29%, CTQ (Critical to Quality) and process capability value in the form of Cpm (Capability Index) for each process stage and yield. Line-5 has DPMO (Defects per Million Opportunities) value of 29,632,607 with a Sigma Score 3.39, and FMEA (Failure Mode and Effect Analysis) analysis resulted in recommendations for improvement at each process stage.Keywords: process cycle efficiency, biscuit, lean six-sigma, CTQ, CpmABSTRAKPenelitian ini bertujuan melakukan analisis tingkat pemborosan (waste/loss) dengan menggunakan pendekatan 7 waste dan value added/non value added activity dalam proses produksi di PT. XYZ. Selanjutnya, melakukan evaluasi terhadap nilai kapabilitas proses produksi dan nilai sigma di PT. XYZ. Penelitian ini menggunakan teknik DMAIC (Define, Measure, Analysis, Improvement, and Control) dari Lean Six Sigma dengan Analisis menggunakan menggunakan alat Failure Mode and Effect Analysis (FMEA). Hasil Penelitian mendapati nilai Process Cycle Efficiency (PCE) 47.29%, CTQ (Critical to Quality) dan nilai kapabilitas proses berupa Cpm (Capability Index) setiap tahapan proses dan Yield. Line-5 memiliki DPMO (Defects Per Million Opportunities) sebesar 29632.607 dengan Sigma Score 3.39 Sigma, analisis FMEA(Failure Mode and Effect Analysis) menghasilkan rekomendasi perbaikan di setiap tahapan proses.Kata kunci: process cycle efficiency, biskuit, lean six sigma, CTQ, Cpm